Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1063/1.2168441
|View full text |Cite
|
Sign up to set email alerts
|

A site-selective in situ study of CO adsorption and desorption on Pt(355)

Abstract: Using time-dependent high-resolution x-ray photoelectron spectroscopy at BESSY II, the adsorption and desorption processes of CO on stepped Pt(355) = Pt[5(111) x (111)] were investigated. From a quantitative analysis of C 1s data, the distribution of CO on the various adsorption sites can be determined continuously during adsorption and desorption. These unique data show that the terrace sites are only occupied when the step sites are almost saturated, even at temperatures as low as 130 K. The coverage-depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
94
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(101 citation statements)
references
References 41 publications
5
94
1
1
Order By: Relevance
“…However, they reported that a critical temperature is needed in order to promote the cracking of the pre-adsorbed molecule, the temperature being dependent on the density of defects on the surface. On the other hand, results regarding CO adsorption on stepped Pt(hkl) surfaces indicate that the process is molecular rather than dissociative 38 . In this sense, our results indicate that the Pt@Au/Au(332) surface has an inherent ability for the dissociation of CO since this process is observed at room temperature.…”
Section: Resultsmentioning
confidence: 93%
“…However, they reported that a critical temperature is needed in order to promote the cracking of the pre-adsorbed molecule, the temperature being dependent on the density of defects on the surface. On the other hand, results regarding CO adsorption on stepped Pt(hkl) surfaces indicate that the process is molecular rather than dissociative 38 . In this sense, our results indicate that the Pt@Au/Au(332) surface has an inherent ability for the dissociation of CO since this process is observed at room temperature.…”
Section: Resultsmentioning
confidence: 93%
“…1a and b the C 1s spectra taken during CO adsorption on Pt(3 2 2) at 150 K and for comparison on Pt(3 5 5) at 130 K [4], respectively, are shown. The total time of the experiment was 1560 s at a pressure of 1.8 · 10 À9 mbar, corresponding to an exposure of 2.81 L.…”
Section: Xp Spectra and Quantitative Analysismentioning
confidence: 99%
“…[3] and references therein) but also, to a lesser extend, on stepped surfaces (Ref. [4] and references therein, Refs. [5,6]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the diffusion can be 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 influenced by the lateral interaction present in the adsorbate layer. In fact, as examined for stepped Pt surfaces, CO adsorbs more strongly in under-coordinated sites than in terrace sites [39][40][41][42] , and the rate of CO filling on under-coordinated is higher as higher is the overall CO coverage. 35 The argument above can be employed, at least in part, to justify why the CO ads does behave like an immobile species during its oxidation.…”
Section: Discussionmentioning
confidence: 99%